Performance enhancement of a statically unstable Two Wheeled Mobile Robot traversing on an uneven surface - Kausar, Zareena; Stol, Karl; Patel, Nitish (2010 IEEE Conference on Robotics, Automation and Mechatronics, 2010)
A Two Wheeled Mobile Robot (TWMR) is a highly nonlinear and open-loop unstable system. Dynamic analysis and control design to keep the body of the robot balanced has been an area of research in the last decade. This problem has been dealt by many researchers for the robot motion on flat surfaces. A few studies have addressed the motion control on constant sloped path. This work studies the control of TWMRs on an uneven surface. With respect to previous results in the literature, the main contributions of this study are the dynamical modeling and control design of a two-wheeled mobile robot while traversing on uneven surface, in particular a single bump. A criterion has been proposed for the system performance evaluation. The system response to a baseline control and proposed Gain Scheduling control is quantified in simulation through proposed criteria. The results show an improvement in system performance on an uneven surface.